Vitamina C em frutos de interesse tecnológico (IV. Comunicação sobre vitamina C) - Cambraia, José; Brune, Walter; Maurício Fortes , José; Andersen , Otto (Revista Ceres, 2025)
By means of adaptation for routine work we analised total vitamin C contents (reduced ascorbic acid plus dehydroascorbic acid) by condensation of its oxydized form with 2,4 dinitrophenylhydrazin (DNP). The color developed by the condensation product was strongly influenced by the sulfuric acid concentration whenused to solubilize the DNP-derivate.